Decoupling sex and intimacy: the role of dissociation in early AIDS prevention campaigns. (3rd July 2019) - Mitchell, Ryan
Abstract: This essay furthers scholarly investigations into how the dissociation of concepts works in actual argumentative contexts. It argues that in moments of biomedical controversy, dissociation can stabilize the epistemic grounds of argument by drawing on taken-for-granted and fundamentally nonscientific forms of evidence. In service of this argument, I explore the role that dissociation plays in paramedical AIDS information materials published before the official recognition of HIV as AIDS's etiological agent in 1984. My analysis illustrates that these texts circumvent the uncertainty surrounding the cause of AIDS by forwarding tentative prevention protocols that dissociate sexuality from intimacy and thus encourage members of at-risk communities to adopt dominant, heteronormative relationship patterns. I conclude by arguing that the dissociation of concepts undergirds biomedicine's ever-broadening epistemic authority—even in moments of palpable uncertainty—by legitimating contingent biomedical knowledge with commonplace social values.